PHYSICAL AND PHYSICO-CHEMICAL METHOD FOR PROCESSING USED BATTERIES - DAESTER, HENRI; GUEBLER, DONAT (1994)
A method comprising physical and physico-chemical steps for processing and recycling used batteries of any shape, size or chemical nature. The physical processing steps comprise turning the batteries into a uniform mass and seprating 35-40 % of the inert residues and directly recyclable metals. The physico-chemical steps of processing the remaining active mass of batteries, i.e. 60-65 % of the overall mass, comprise removing toxic contaminants such as mercury and cadmium, purifying and separating the manganese oxides in the form of a sludge which may be recycled or turned into an inert residue, then purifying and separating the zinc compounds in the form of a metallurgically or electrolytically recyclable hydroxide sludge to obtain metal with a purity of 99.5 % or higher. According to an alternative embodiment of the physico-chemical processing of the remaining active mass of batteries, the zinc is extracted as a directly electrolysable sulphuric solution whereas the manganese oxides and the impurities are turned into granules stabilised by means of an immobilisation method using cement. Un procédé comportant des opérations physiques et physico-chimiques destiné au traitement - recyclage des piles et batteries usagées de toute forme, de toute taille et de toute nature chimique. Les traitements physiques permettent de transformer les piles et batteries en une masse uniforme et d'en séparer 35 à 40 % de résidus inertes et métaux directement recyclables. Les traitements physico-chimiques de la masse active restante des piles et batteries, soit entre 60 et 65 % de la masse totale, permettent d'éliminer les contaminants toxiques tels que le mercure et le cadmium, de purifier et de séparer les oxydes de manganèse sous forme de boue recyclable ou transformable en résidu inerte, et finalement de purifier et de séparer les composés de zinc sous forme de boue d'hydroxyde recyclable par voie métallurgique ou par électrolyse sous forme de métal d'une pureté de 99,5 % ou plus. Une variante de traitement physico-chimique de la masse active restante des piles et batteries permet d'extraire le zinc sous forme de solution sulfurique directement électrolysable, les oxydes de manganèse avec les impuretés étant transformés en granules stabilisées par un procédé d'immobilisation avec du ciment.